Lenalidomide after Stem-Cell Transplantation for Multiple Myeloma - McCarthy, Philip L; Owzar, Kouros; Hofmeister, Craig C; Hurd, David D; Hassoun, Hani; Richardson, Paul G; Giralt, Sergio; Stadtmauer, Edward A; Weisdorf, Daniel J; Vij, Ravi; Moreb, Jan S; Callander, Natalie Scott; et al. (The New England journal of medicine, 2012)
In patients who had undergone stem-cell transplantation, lenalidomide maintenance therapy improved progression-free and overall survival, though at the expense of some increased hematologic toxicity and second malignant tumors. A goal of therapy for multiple myeloma, to induce complete remission and prolong survival, is usually accomplished with combination therapy. 1 , 2 Autologous hematopoietic stem-cell transplantation is often used after induction chemotherapy to improve the response or to consolidate complete remission. 1 , 2 However, since most patients with multiple myeloma have disease recurrence or progression after transplantation, maintenance therapies have been used to prolong complete remission and prevent relapse or progressive disease. Low-dose melphalan, interferon alfa, and glucocorticoids have been used for maintenance after primary therapy, but their long-term use is limited by toxicity and modest efficacy. 3 – 6 Five studies involving patients who . . .